2018
DOI: 10.1126/science.aan4074
|View full text |Cite
|
Sign up to set email alerts
|

Dentate gyrus mossy cells control spontaneous convulsive seizures and spatial memory

Abstract: Temporal lobe epilepsy (TLE) is characterized by debilitating, recurring seizures and an increased risk for cognitive deficits. Mossy cells (MCs) are key neurons in the hippocampal excitatory circuit, and the partial loss of MCs is a major hallmark of TLE. We investigated how MCs contribute to spontaneous ictal activity and to spatial contextual memory in a mouse model of TLE with hippocampal sclerosis, using a combination of optogenetic, electrophysiological, and behavioral approaches. In chronically epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
255
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(291 citation statements)
references
References 32 publications
(52 reference statements)
25
255
10
1
Order By: Relevance
“…The three IHKA groups displayed deficits in the OLM task compared to nonepileptic controls at 10 days post‐IHKA (control: DI = 29.5 ± 2.2, n = 6; IHKA: DI = 5.9 ± 4.6, n = 10, P < .001), 3‐4 months post‐IHKA (control: DI = 35.6 ± 4.0, n = 5; IHKA: DI = 11.0 ± 2.8, n = 9, P = .002), and 6‐7 months post‐IHKA (control: DI = 30.6 ± 3.7, n = 14; IHKA: DI = 7.9 ± 2.0, n = 9, P < .001) (Figure B, Table ). As we showed in a previous study, IHKA mice displayed deficits compared with nonepileptic controls and did not discriminate effectively between the moved and unmoved object (DI < 20). Quantification of the total exploration time of the objects remained the same between IHKA‐treated and control animals at 10 days (control: 4.0 ± 0.4 s; IHKA: 4.5 ± 0.3 s), 3‐4 months after IHKA (control: 3.9 ± 0.4 s; IHKA: 4.1 ± 0.2 s), and 6‐7 months after IHKA (control: 5.0 ± 0.2 s; IHKA: 4.5 ± 0.4 s), indicating that the deficit in OLM performance in IHKA animals was not due to lack of exploration (Figure C).…”
Section: Resultssupporting
confidence: 69%
“…The three IHKA groups displayed deficits in the OLM task compared to nonepileptic controls at 10 days post‐IHKA (control: DI = 29.5 ± 2.2, n = 6; IHKA: DI = 5.9 ± 4.6, n = 10, P < .001), 3‐4 months post‐IHKA (control: DI = 35.6 ± 4.0, n = 5; IHKA: DI = 11.0 ± 2.8, n = 9, P = .002), and 6‐7 months post‐IHKA (control: DI = 30.6 ± 3.7, n = 14; IHKA: DI = 7.9 ± 2.0, n = 9, P < .001) (Figure B, Table ). As we showed in a previous study, IHKA mice displayed deficits compared with nonepileptic controls and did not discriminate effectively between the moved and unmoved object (DI < 20). Quantification of the total exploration time of the objects remained the same between IHKA‐treated and control animals at 10 days (control: 4.0 ± 0.4 s; IHKA: 4.5 ± 0.3 s), 3‐4 months after IHKA (control: 3.9 ± 0.4 s; IHKA: 4.1 ± 0.2 s), and 6‐7 months after IHKA (control: 5.0 ± 0.2 s; IHKA: 4.5 ± 0.4 s), indicating that the deficit in OLM performance in IHKA animals was not due to lack of exploration (Figure C).…”
Section: Resultssupporting
confidence: 69%
“…To examine if the effects of inhibitory and excitatory DREADDs are specific to ventral but not dorsal MCs, we injected AAVs expressing mCherry, Hm4Di-mCherry or Hm3Dq-mCherry bilaterally into the dorsal hilus of Drd2-cre mice expressing Cre in dorsal MCs (Puighermanal et al, 2015). We confirmed that all mCherry-expressing cells are positive for GluR2/3, a marker for dorsal MCs (Fujise et al, 1997) ( (Bui et al, 2018;Hsu et al, 2016), these results indicate that the activation of longrange projections of ventral MCs has an excitatory net effect on dorsal GCs and further support our anatomical findings.…”
Section: Ventral Mcs Activity Is Required For Dorsal Gcs Activation Dmentioning
confidence: 72%
“…Given that only a partial ipsilateral population of dorsal MCs is labeled in our experiments, the high percentage (23.6 %) of labeled synapses on PV+ dendrites implies that the majority of excitatory inputs on these interneurons in the inner ML derive from dorsal MCs, and only a minor population from ventral MCs. Thus, ventral MCs may exert a net excitatory effect on dorsal GCs in contrast to the net inhibitory effect exerted by dorsal MCs (Bui et al, 2018;Hsu et al, 2016).…”
Section: Ventral Mcs Make Extensive Excitatory Synaptic Contacts Withmentioning
confidence: 96%
“…Our study suggests that MC loss in these conditions, even in a small number, could potentially lead to aberrant hippocampal neurogenesis and associated cognitive deficits. Furthermore, a recent study demonstrated that activation of remaining MCs after chronic temporal lobe epilepsy alleviates seizure severity; while inhibition of those MCs impairs cognitive functions (Bui et al, 2018). Therefore, targeting the MC circuit by enhancing the indirect pathway or dampening the direct pathway may constitute a therapeutic strategy to combat hippocampal hyperexcitability associated with various neurological disorders and brain injuries in order to preserve neural stem cell pool, maintain sustainable hippocampal neurogenesis, and promote cognitive functions.…”
Section: Discussionmentioning
confidence: 99%